Multi-Dimensional Analysis of Spatio-Temporal Correlation Information: Development of Higher-Order Algorithm of PIV Analysis - KIRIMOTO, Kensuke; NISHIO, Shigeru (Transactions of Visualization Society of Japan, 2009)
The new concept for multi-dimensional PIV analysis of spatio-temporal correlation information is proposed, and the idea was applied to the development of an algorithm for higher-order analysis of multi-frame PIV images. The PIV enabled us to obtain the instantaneous field data of flow velocity, but the measurement principles remain at the stage of point by point analysis. The authors have proposed utilizing the spatio-temporal sequential image data change, and the field analysis of correlation information was examined. The developed algorithm analyzes the multi-frame correlation information systematically. The correlation information was evaluated by accumulating the correlation information along path lines, and the successive spatio-temporal velocity changes were detected together with its derivatives. The performance of present algorithm was evaluated by means of VSJ standard image. Present approach shows superior performance than the conventional method.